Readers reading practices of EFL Yemeni students: recommendations for the 21st century - Hazita Azman; Abdullah Mohammad Bhooth; Kemboja Ismail (Penerbit UKM, 2013)
This paper investigates the reading practices of forty-five second year EFL Yemeni undergraduate students using the Four Resources Model of multiliteracy practices. The Four Resources Model of multiliteracy practices organizes reading practices into four key practices: code breaking, text participating, text uses and text analysing levels. Quantitative and qualitative methods, designed based on the Four Resources Model constructs, were used to collect data from a sample of students studying English as a Foreign Language at a university in Yemen. Quantitative data was collected through a questionnaire, while qualitative data was gathered using semi-structured interviews guided by the research objectives. The findings reveal that Yemeni students were medium users of the code breaker and text user practices whereas the meaning making and text analysis practices were reported to be used in low usage. On the whole, these early findings suggest that the reading practices and reading abilities of the Yemeni students are still limited even at the tertiary level and have not developed fully with regard to reading in English. This paper reports in detail, the use of the Four Resources Model as a tool to determine reading efficacy while examining the aforementioned findings. Discussion is put forward on the implications for teaching of reading and its approaches in a Yemeni context, especially in view of the students‟ reading needs at the tertiary level in Yemen.